Pendekatan Komunikasi Guru Dalam Interaksi Sosial Dengan Siswa Tunarungu : Studi Di SLB B Tunarungu Wicara YPAC Palembang - Mei Pertama Putri; Kun Budianto; Putri Citra Hati (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
The school environment requires each other to interact and communicate every day. The problem in research is that deaf students who have hearing impairments need knowledge to be able to coexist with society. Teachers really need the right communication approach so that students can understand what is being conveyed so that there will be a reciprocal relationship between the two. The purpose of this research is to determine teachers' communication approaches in social interactions with deaf students. This research explains how a communication approach is important in the social interactions of deaf students through interactions in classroom learning and also in the school environment. This research uses qualitative research methods using Burgoon's interaction adaptation theory which discusses nine principles in adaptation. This research uses data collection techniques in the form of observation, interviews and documentation techniques. The results of this research are that adaptation in the communication approach in social interaction of deaf students requires adapting interaction patterns, varying distance patterns and strategies as well as the importance of behavior in adaptation. Apart from that, in the communication approach the teacher determines communication media in the learning process in the classroom and provides direction to students to increase social interaction. Learning to develop sound and rhythm perception as well as speech development, these activities are efforts made by the school to increase social interaction for deaf students. Communication patterns in teaching at SLB B YPAC Palembang are two-way communication.